1999
DOI: 10.1177/002215549904700105
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase in the Gills of Seawater-and Freshwater-acclimated Flounders Platichthys flesus: Purification, Characterization, and Immunohistochemical Localization

Abstract: SUMMARYFlounders Platichthys flesus were investigated with respect to isolation, purification, and cellular localization of carbonic anhydrase (CA) in the respiratory system. CA was purified from gills and erythrocytes and was shown to exclusively represent a soluble enzyme with an apparent molecular weight of 30 kD. Inhibition constants (K I ) towards acetazolamide (ACTZ) were 8.4·10 Ϫ 9 M for erythrocyte CA and 7.6·10 Ϫ 9 M for gill CA, indicating a high sensitivity to sulfonamides, as exhibited by human CA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…Immunocytochemical localization of branchial CA using an antibody raised against purified trout gill CA confirmed the broad distribution reported by Conley and Mallatt (1988) and additionally indicated that CA was concentrated in the apical region of both pavement cells and MR cells (Rahim et al, 1988). However, these patterns are not true of all species examined to date; in some species CA appears to be confined to either pavement cells or MR cells, while in others it is found in both (Dimberg et al, 1981;Conley and Mallatt, 1988;Flügel et al, 1991;Sender et al, 1999;Wilson et al, 2000b,c;Hirata et al, 2003;Choe et al, 2004).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Immunocytochemical localization of branchial CA using an antibody raised against purified trout gill CA confirmed the broad distribution reported by Conley and Mallatt (1988) and additionally indicated that CA was concentrated in the apical region of both pavement cells and MR cells (Rahim et al, 1988). However, these patterns are not true of all species examined to date; in some species CA appears to be confined to either pavement cells or MR cells, while in others it is found in both (Dimberg et al, 1981;Conley and Mallatt, 1988;Flügel et al, 1991;Sender et al, 1999;Wilson et al, 2000b,c;Hirata et al, 2003;Choe et al, 2004).…”
Section: Discussionsupporting
confidence: 79%
“…evidence indicates that branchial cytoplasmic CA is present in both pavement and MR cells, with a generally apical location (Rahim et al, 1988;Sender et al, 1999;Wilson et al, 2000b). Rahim et al (1988) also provided immunological evidence for the presence of distinct branchial and blood CA isoforms in rainbow trout and carp, a finding that was recently confirmed by the cloning of rainbow trout blood (tCAb) and cytosolic (tCAc) CA isoforms (Esbaugh et al, 2004(Esbaugh et al, , 2005.…”
Section: Introductionmentioning
confidence: 81%
“…Branchial CA activity is thought to be largely cytoplasmic, occurring primarily in pavement cells and chloride cells (Lacy, 1983;Conley and Malalatt, 1988;Rahim et al, 1988;Flügel et al, 1991;Sender et al, 1999;Wilson et al, 2000), with the exception of membrane bound isozymes found in the gills of elasmobranchs (Swenson and Maren, 1987;Gilmour et al, 1997Gilmour et al, , 2001Gilmour et al, , 2002Henry et al, 1997;Wilson et al, 2000), and Antarctic fishes, Chaenocephalus aceratus and Notothenia coriiceps . Evidence is mixed on whether the same CA isozyme ·The Journal of Experimental Biology 208, 1951Biology 208, -1961 Published by The Company of Biologists 2005Biologists doi:10.1242 It is well established that the gills of teleost fish contain substantial levels of cytoplasmic carbonic anhydrase (CA), but it is unclear which CA isozyme(s) might be responsible for this activity.…”
mentioning
confidence: 99%
“…Recently, the presence of carbonic anhydrase (Sender et al 1999;Gilmour et al 2007), ammonia transporter (Nakada et al 2007), and a member of the winged helix/forkhead transcription factor FoxF1 (Hidaka et al 2004), which is required for normal development of lung and foregut in mammals (Mahlapuu et al 2001), have been demonstrated in pillar cells. These observations, as well as the results of this study, have highlighted the importance of pillar cells in respiration and nitrogen metabolism.…”
Section: Discussionmentioning
confidence: 99%